Solid waste identification in green areas at the Faculty of Geological, Mining, Metallurgical and Geographical Engineering of the National Mayor University of San Marcos - Paredes Del Pino, Eddie Daniel (2023)
The research seeks to analyze the contamination of green areas by solid waste in the School of Geological, Mining, Metallurgical and Geographic Engineering due to the importance of these spaces in the integral development of students. This work included field visits, surveys and the analysis and description of the data collected. It was determined that the most common type of waste found in these areas was plastic, followed by cardboard and paper, and that although the results of the survey show that 100% of the students consider the proper management of solid waste in green areas to be very important, 42% admit to having thrown or abandoned garbage in these spaces. This work is intended to be a starting point for the development of good environmental management of solid waste in order to achieve a healthy and clean environment.